Analisis Metode yang Digunakan Guru Kelas dalam Memotivasi Belajar Siswa di SD N I Basuhan - Ristanto (Fakultas Agama Islam, 2015)
Analisis Metode yang Digunakan Guru Kelas dalam Memotivasi Belajar Siswa di SD N I Basuhan